Cerebral venous sinus thrombosis: changing trends in the incidence, age and gender (findings from the CMC Vellore CVT registry) - Vivek Mathew; Mahasampath Gowri; Sanjith Aaron; Ajith Sivadasan; George Abraham Ninan; Rohit N Benjamin; Appaswamy Thirumal Prabhakar; Angel Miraclin T; John Davis Prasad; Deepti Bal; Atif Iqbal Ahmed Shaikh (Stroke and Vascular Neurology)
Background Multiple cerebral venous sinus thrombosis (CVT) registries from various geographical regions indicate that female gender, the use of contraceptive pills, pregnancy and puerperium are important risk factors. In this study, we report the changes in the epidemiology of patients with CVT managed over the past 26 years.Methods The CMC Vellore CVT registry is a prospectively maintained database at the Christian Medical College, Vellore since January 1995. Stata software was used to analyse the data and assess the changes in the incidence, age and gender distribution over the previous 26 years.Results Among 1701 patients treated during the study period, 908 (53%) were women and 793 (47%) were men. The mean incidence of CVT was 49 per 100 000 admissions before 2010, which increased to 96 per 100 000 after 2010. Male gender had a higher odds of developing CVT (OR – 2.07 (CI 1.68 to 2.55, p<0.001). This could be attributed to the declining incidence of postpartum CVT after 2010 compared with the decade before 2010 (50% vs 20%). The mean age at presentation had increased from 24.5 to 33.2 years in the last decade.Conclusions There was a clear change in the gender pattern from being a condition with female preponderance, to one where equal or more men are being affected. Lower incidence of postpartum CVT cases could be the driving factor. An increase in the overall incidence of CVT cases was noted, probably due to a higher index of clinical suspicion and better diagnostic imaging modalities.